UTILIZING ARTIFICIAL INTELLIGENCE TO EVALUATE STUDENTS’ COMPETENCY IN WRITING SIMPLE PAST TENSE - Antara, I Made Agung Rai; Anggreni, Ni Putu Yunik (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2024)
Abstract The purpose of this study is to determine the application of artificial intelligence (Copilot) in evaluating student writing in writing simple past tense. The method of this research is qualitative. The data collection technique was carried out by collecting 5 student writings randomly. The data analysis technique was carried out with qualitative descriptive method. The results showed that the copilot was able to create a rubric used to evaluate students' writing in writing simple past tense. This rubric consists of several parts, namely content development, organization, grammar and mechanics, usage and style. The results showed that copilots were able to evaluate well, such as being able to identify topic coverage, relevance, paragraph structure, transitions, sentence structure, spelling and punctuation, verb tense consistency and word choice. The feedback provided by Copilot is able to describe writing errors well and in detail. Teachers are advised to utilize artificial intelligence in the learning process, especially in evaluating student writing. Teachers can explore the use of artificial intelligence and its capabilities in language learning so that they can work more easily and effectively. Teachers can integrate AI tools such as Copilot into the assessment process, particularly grammar and tenses. The developer of AI should continuously refine AI capability to give more sophisticated feedback on complex transitions and sentence structures. Keywords: Writing, artificial Inteliggence, Assesment